Bahasa Indonesia: Bahasa Indonesia - Abidin, Ahmad Zainul; Dantes, Komang Febrinayanti; Suastika, I Nengah (Universitas Pendidikan Ganesha, 2024)
Abstract This research aims to find out, (1) how the regulations regarding land ownership disputes that are occupied unlawfully according to Indonesian Civil Law are regulated, and (2) how the Judge considers them in Decision Number 5/Ptg.G/2019/PN Krs who adjudicates dispute cases related to land grabbing in Temenggungan village. The type of research used is normative juridical which has a qualitative descriptive nature. The type of research approach involves a statutory approach, a conceptual approach and a case approach. The data collection technique used is document study, case approach, legislation. The results of the research show that (1) Regarding disputes over land ownership that is occupied unlawfully by Indonesian Civil Law, it has been regulated in Government Regulation No. 5 of 1960 concerning Agrarian Principles and No. 51 of 1960 concerning the prohibition of using land without permission, as well as Government Regulation No. 24 of 1997. As a result of the many regulations, the resolution of ownership disputes that are illegally occupied uses the legal basis of Article 160 HIR, Article 1865 KHPerdata, Article 1925 KHPerdata, Article 1361 Civil Code, and Decision of the Supreme Court of the Republic of Indonesia Number: 3909 K/Pdt/1994. (2) In the judge's decision Number 5/Ptg.G/2019/PN Krs, it is stated that the plaintiff is the legal owner of the 1330M² plot of land as stated in the sale and purchase deed Number 210/JB/KREJENGAN/VII/2007, dated 12 July 2007 , made by PUDJI ASTUTI, SH. PPAT in Kraksaan.